2010
DOI: 10.1177/0363546510365296
|View full text |Cite
|
Sign up to set email alerts
|

Repair of Chronic Osteochondral Defects Using Predifferentiated Mesenchymal Stem Cells in an Ovine Model

Abstract: The results suggest an encouraging method for future treatment of focal osteochondral defects to prevent progression to osteoarthritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
157
1
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(164 citation statements)
references
References 36 publications
(43 reference statements)
4
157
1
2
Order By: Relevance
“…Chondrogenic priming of MSCs to generate a more functional cartilage-like graft prior to implantation has been shown to improve the quality of repair in animal model 48,49 Translating such therapies to treat damaged and diseased articular cartilage in man will most likely necessitate the development of tissue engineering strategies to generate functional cartilaginous grafts using autologous stem cells. The objective of this study was to explore how environmental factors during both the expansion and differentiation of diseased human FPSCs would influence their chondrogenic capacity following encapsulation into three-dimensional hydrogels.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Chondrogenic priming of MSCs to generate a more functional cartilage-like graft prior to implantation has been shown to improve the quality of repair in animal model 48,49 Translating such therapies to treat damaged and diseased articular cartilage in man will most likely necessitate the development of tissue engineering strategies to generate functional cartilaginous grafts using autologous stem cells. The objective of this study was to explore how environmental factors during both the expansion and differentiation of diseased human FPSCs would influence their chondrogenic capacity following encapsulation into three-dimensional hydrogels.…”
Section: Discussionmentioning
confidence: 99%
“…43,44 While the use of MSCs has been shown to improve repair compared with untreated controls, critically normal hyaline cartilage does not regenerate, rather a hyaline-like or fibro-cartilagenous tissue forms. [45][46][47] Chondrogenic predifferentiation of MSCs within collagen gels, leading to improved functionality of the engineered graft prior to implantation, has been shown to improve the outcome in long-term sheep studies, 48 resulting in superior repair compared with undifferentiated MSCs or chondrocytes. 49 While promising, the quality of repair observed in these animal model studies using predifferentiated MSCs is still variable, 48,49 suggesting that engineering a more functional graft may be required prior to implantation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, an experimental study showed superior results with in vivo cartilage repair when prior in vitro chondrogenic differentiation was induced. 37 Based on these findings, this study describes a novel triphasic construct for repair of deep osteochondral defects using a collagen I scaffold seeded with chondrogenically differentiated MSCs, an intermediate layer of autologous plasma and a porous, seeded ␤-TCP cylinder. This implant was compared to the clinically established OATS technique using a validated large animal model for degenerated critical-size cartilage defects.…”
Section: Journal Of Orthopaedic Research December 2010mentioning
confidence: 99%
“…Studies using predifferentiated MSCs for cartilage repair have resulted in faster and better cartilage regeneration compared with the use of undifferentiated MSCs, with phenotype stability maintained up to 1 year postimplantation [11,12]. These studies indicate that preconditioned MSCs can be employed to overcome the requirement of an extended regeneration period and to improve the quality of the neocartilage from the often inferior quality derived from undifferentiated MSCs [13,14].…”
Section: Introductionmentioning
confidence: 97%